PEMBUATAN DAN PENGUJIAN SENSOR ULTRASONIK SEBAGAI FEEDBACK PADA SISTEM KENDALI OTOMATIK PITCH ATTITUDE HOLD - Zaeny, U. M; Indriyanto, T; Muhammad, H (Mesin, 2007)
Standard altimeter, i.e. static tube, does not work accurate enough for vehicle flying several meters from the ground. One alternative for measuring altitude in this case is using ultrasonic range-meter. This idea is brought further by using two range-meters to measure pitch attitude. Laboratory experiments were conducted to study this idea statically by constructing them in an inclined moving bar and dynamically by arranging them in a Pitch Attitude Hold control system.